A Response Surface Model Exploration of Dosing Strategies in Gastrointestinal Endoscopies Using Midazolam and Opioids. Issue 23 (June 2016) - Liou, Jing-Yang; Ting, Chien-Kun; Hou, Ming-Chih; Tsou, Mei-Yung
Abstract : Abstract: Classical midazolam–opioid combination for gastrointestinal endoscopy sedation has been adopted for decades. Dosing regimens have been studied but most require fixed dosing intervals. We intend to use a sophisticated pharmacodynamic tool, response surface model (RSM), to simulate sedation using different regimens. RSM can predict patient's response during different phases of the examination and predict patient's wake-up time with precision and without the need for fixed dosing intervals. We believe it will aid physicians in guiding their dosing strategy and timing. The study is divided into 2 parts. The first part is the full Greco RSMs development for 3 distinct phases: esophagogastroduodenoscopy (EGD), colonoscopy, and intersession (the time lapse between procedures). Observer's Assessment of Alertness Score (OAA/S) is used to assess patient response. The second part simulates 6 regimens with different characteristics using the RSMs: midazolam only, balanced midazolam and opioids, high-dose opioids and midazolam, low-dose midazolam with high-dose opioids, high-dose midazolam and low-dose opioids, and finally midazolam with continuous opioid infusion. Loss of response at 95% probability for adequate anesthesia during examination and return of consciousness at 50% probability during intersession was selected for simulation purposes. The average age of the patient population is 49.3 years. Mean BMI is 21.9 ± 2.3 kg/m 2 . About 56.7% were females and none received prior abdominal surgery. The cecal intubation rate was 100%. Only 1 patient (3%) developed temporary hypoxemia, which was promptly managed with simple measures. The RSMs for each phase showed significant synergy between midazolam and alfentanil. The balanced midazolam and alfentanil combination provided adequate anesthesia and most rapid return of consciousness. The awakening time from the final drug bolus was 7.4 minutes during EGD and colonoscopy stimulation, and 9.1 minutes during EGD simulation. Simulation of regimens with different characteristics gives insights on dosing strategies. A balanced midazolam–alfentanil regimen is adequate in providing good anesthetic depth and most rapid return of consciousness. We believe with the aid of our RSM, clinicians can perform sedation with more flexibility and precision.